PFAS in Australian raptor species: terrestrial biomonitors of environmental contamination in changing ecosystems - Phoebe Lewis; Christopher P. Johnstone; Timothy Chaston; Jordan O. Hampton; Judy Clarke; John Leeder; Yan Wang; Matthew Etterson; Jennifer Martin; Minna Saaristo (Environmental Pollution, 2026)

The effects of release failure conditions on jet impingement ignition of pressurised hydrogen jets - David J. Willmore; Jordan A.C. Kildare; Paul R. Medwell; Timothy C.W. Lau; Michael J. Evans (Fuel, 2026)

Leaf Size in Conifers: Global Associations With Climate and Evolutionary History - Katya I. Bandow; Timothy J. Brodribb; Benjamin Halliwell; Matilda J. M. Brown; Kate M. Johnson; Gregory J. Jordan (Global Change Biology, 2026)
Global analyses of leaf size suggest that large leaves predominate in favourably warm and wet climates, and small leaves occur at climatic extremes. However, these patterns are dominated by data from angiosperms and may obscure drivers of leaf size variation in older, less speciose groups, such as conifers. Here we employ a novel modelling framework, multi‐response phylogenetic mixed models (MRPMM), that identifies trait correlations at both phylogenetic and phylogenetically independent levels to investigate how climate influences leaf size evolution across conifers. We show overall patterns for all conifers and focus on three groups with distinctive leaf architectures: scale‐leaved Cupressaceae, needle‐leaved Pinus and broad‐leaved Podocarpus . We found moderate to strong phylogenetic signal in conifer leaf and climate niche traits. Phylogenetic relationships explained most of the association between leaf size and climate, with temperature revealed as a stronger driver than dry season precipitation, indicating deep‐time co‐evolutionary associations. These patterns reflect trade‐offs associated with leaf hydraulic architecture under contrasting selection pressures. In single‐veined leaves, lateral water transport and thus leaf width is constrained, yet this narrow leaf form can be advantageous for survival under climatic extremes such as drought and freezing. In contrast, anatomical innovations (like accessory transfusion tissue in Podocarpus ) allow for broader leaves which are favourable in competitive environments, while also potentially making leaves more vulnerable to climate extremes. Our results support previous evidence for phylogenetic niche conservatism in conifers, where species tend to track their ancestral climatic preferences rather than adapting to new environments. This conservatism, likely controlled by leaf hydraulic architecture, results in strong evolutionary constraints on current bioclimatic distributions and potential responses to changing climates in conifers. This study also highlights the importance of considering phylogenetic impacts on functional trait evolution, especially in evolutionarily conservative groups like conifers.

Evaluation of coal combustion residuals in cement systems - Ashish D. Patel; Jordan K. Magnuson; Timothy G. Townsend; Christopher C. Ferraro (Journal of Hazardous Materials, 2026)

Lynch syndrome integrative epidemiology and genetics (LINEAGE): rationale for cohort design - Swati G. Patel; Holli A. Loomans-Kropp; Zachariah H. Foda; Bryson W. Katona; Suzi Birz; Carol A. Burke; Jordan Clawson; Brian Furner; Camille Hochheimer; Elizabeth Magnan; Luigi Ricciardiello; Harminder Singh; et al. (Familial Cancer, 2026)

Optimization of pretreatments for municipal solid waste incineration ash reuse in cement manufacture: A critical review - Jordan K. Magnuson; Christopher C. Ferraro; Timothy G. Townsend (Resources, Conservation and Recycling, 2026)

Small amphipathic amino acids imprint the active site of extant E. coli aminoacyl-tRNA synthetases - Douglas Iverson; Crystal Serrano; Kalii Faustino; Elena Hauf-Pisoni; Timothy Jordan; Japeth Mobisa; Dhathry Doppalapudi; Amran Mohamed; Nicholas Panuco; Daniel Ghebreigziabher; Anthony J. Bell (BioSystems, 2026)

Cognitive and affective empathy, executive functions, and the key role of personal distress: Why do autistic traits predict mental health symptoms in neurotypical adults? - Dilruba Sönmez; Timothy R. Jordan (Cognitive Processing, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Environmental analysis of a ten-year pilot project using municipal solid waste incinerator bottom ash as road base: a case study - Jordan K. Magnuson; Kate D. Weiksnar; Steven J. Laux; Justin G. Roessler; Christopher C. Ferraro; Timothy G. Townsend (Resources, Conservation and Recycling, 2026)

Seascape diversity and configuration shape habitat selection across multiple coastal ecosystems - Jesse D. Mosman; Hayden P. Borland; Ashley J. Rummell; Christopher J. Henderson; Sam Allan; Alec Bannam; Stacy L. Bierwagen; Michael J. Bradley; Alex B. Carter; Daniela M. Ceccarelli; Robert Coles; Michael J. Emslie; et al. (Biological Conservation, 2026)

The potential for unwanted genetic rescue in invasive fallow deer populations - Lauren C. White; Erin Hill; Eliane D. McCarthy; Andrew J. Bengsen; Sebastien Comte; Sandie Czarka; David M. Forsyth; Catherine E. Grueber; Jake Haddad; Jordan O. Hampton; Michelle Hanslow; Scott Jennings; et al. (Biological Invasions, 2026)

Evaluation of alkali-silica reactivity behavior and mitigation in waste-to-energy bottom ash for sustainable aggregate use in concrete - Kate D. Weiksnar; Jordan K. Magnuson; Ashish D. Patel; Robbie Posada; Christopher C. Ferraro; Timothy G. Townsend (Waste Management, 2025)

Toxin uptake and slowed reflexes by the marine snail Lunella undulata following exposure to paralytic shellfish toxin producing Alexandrium catenella - Andreas Seger; James Brady; Kellen S. Vandeveer; Timothy Jordan; Andrew J. Trotter; Grace Robinson; John P. Keane; Alison Turnbull (Harmful Algae, 2025)

A Synthesis of Factors Related to Trends in Abundance and Demography of Alaska Chinook Salmon ( Oncorhynchus tshawytscha , Salmonidae): Implications for Research, Management, and Policy - Chase C. Lamborn; Jan Ohlberger; Timothy E. Walsworth; Peter A. H. Westley; Curry J. Cunningham; Sam Wynsma; Jordan W. Smith (Fish and Fisheries, 2025)
Across Alaska, there have been synchronous declines in the abundance, mean age, and size of Chinook salmon ( Oncorhynchus tshawytscha , Salmonidae), a species with immense social and ecological importance. The decline of Chinook salmon, and regulations addressing declines, have drastically impacted people who rely on Alaska's fisheries. Despite their importance, the drivers causing Chinook salmon declines are still not well understood. Therefore, to improve our understanding of the likely drivers of these large‐scale synchronous declines, we synthesised the peer‐reviewed Chinook salmon literature published between 2010 and 2024 using a weight‐of‐evidence approach. We identified 94 variables used to explain the trends in abundance and demographics of Chinook salmon. Each variable's association with trends in Chinook salmon was individually assessed and integrated using a standardised method. Results of this synthesis suggest the drivers for large‐scale synchronous declines have occurred in the North Pacific Ocean. Specifically, we found marine predation, size selective harvest, and pink salmon ( Oncorhynchus gorbuscha ) abundance are the factors most strongly associated with reduced size and age. Results also suggest ocean productivity–specifically winter sea surface temperature and the North Pacific Gyre Oscillation–are the most frequently identified predictors of regional Chinook salmon abundance. In addition to addressing freshwater factors like adult heat stress and juvenile predation, we suggest research, policy, and management focus on how to better understand and address the interactions between ocean productivity, marine predation, size selective harvest, and pink salmon abundance to improve the condition of Chinook salmon, and the people and ecosystems benefiting from them.

The impact of air pollution on sperm DNA methylation - Jordan L. Moore; Seth J. Parks; Emma R. James; Kenneth I. Aston; Timothy G. Jenkins (Reproductive Toxicology, 2025)

The genus Hypobathrum (Rubiaceae) in Thailand - Sawita Yooprasert; Jordan Bilsborrow; Timothy M. A. Utteridge (Kew Bulletin, 2024)
Summary The genus Hypobathrum in Thailand is revised, based on the morphological characters found in herbarium specimens from Thailand and neighbouring countries including Bangladesh, Myanmar, Cambodia and Peninsular Malaysia. In this study, three species of Hypobathrum are recognised, among them, H. venulosum is a newly recorded species in this region. An identification key is provided for the species, along with descriptions, synonyms, distribution ranges and vernacular names (if available).

Australian non-perennial rivers: Global lessons and research opportunities - Margaret Shanafield; Melanie Blanchette; Edoardo Daly; Naomi Wells; Ryan M. Burrows; Kathryn Korbel; Gabriel C. Rau; Sarah Bourke; Gresley Wakelin-King; Aleicia Holland; Timothy Ralph; Gavan McGrath; et al. (Journal of Hydrology, 2024)

Insights on volatile metals in landfill gas as determined from advanced treatment media - Thomas J. Smallwood; Jordan K. Magnuson; Jake T. Thompson; Ashley M. Lin; Timothy G. Townsend (Journal of Hazardous Materials, 2024)

Processing municipal solid waste incineration bottom ash for integration into cement product manufacture - Jordan K. Magnuson; Kate D. Weiksnar; Ashish D. Patel; Kyle A. Clavier; Christopher C. Ferraro; Timothy G. Townsend (Resources, Conservation and Recycling, 2023)

Effect of waste-derived soil amendments on mitigating leaching impacts from municipal solid waste incineration (MSWI) ash - Chad J. Spreadbury; Jordan K. Magnuson; Kyle A. Clavier; Steven J. Laux; Timothy G. Townsend (Waste Management, 2023)

Emerging polycyclic aromatic hydrocarbon (PAH) and trace metal leachability from reclaimed asphalt pavement (RAP) - Ashley M. Lin; Alina S. Timshina; Jordan K. Magnuson; John A. Bowden; Timothy G. Townsend (Chemosphere, 2023)

Elevated lead exposure in Australian hunting dogs during a deer hunting season - Jordan O. Hampton; Mia L. Cobb; Simon D. Toop; Jason S. Flesch; Timothy H. Hyndman (Environmental Pollution, 2023)

Great expectations: patients’ preferences for clinically significant results from genomic sequencing - Salma Shickh; Agnes Sebastian; Marc Clausen; Chloe Mighton; Christine Elser; Andrea Eisen; Larissa Waldman; Seema Panchal; Thomas Ward; June C. Carroll; Emily Glogowski; Kasmintan A. Schrader; et al. (Human Genetics, 2023)

Integrating management of marine activities in Australia - Robert L. Stephenson; Alistair J. Hobday; Ian Butler; Toni Cannard; Mel Cowlishaw; Ian Cresswell; Christopher Cvitanovic; Jon C. Day; Kirstin Dobbs; Leo X.C. Dutra; Stewart Frusher; Maree Fudge; et al. (Ocean & Coastal Management, 2023)

White matter tract conductivity is resistant to wide variations in paranodal structure and myelin thickness accompanying the loss of Tyro3: an experimental and simulated analysis - Farrah Blades; Jordan D. Chambers; Timothy D. Aumann; Christine T. O. Nguyen; Vickie H. Y. Wong; Andrea Aprico; Eze C. Nwoke; Bang V. Bui; David B. Grayden; Trevor J. Kilpatrick; Michele D. Binder (Brain Structure and Function, 2022)

No‐analogue associations in the fossil record of southern conifers reveal conservatism in precipitation, but not temperature axes - Matilda J. M. Brown; Timothy J. Brodribb; Gregory J. Jordan (Global Ecology and Biogeography, 2021)
Aim Southern conifers have evolved under different evolutionary pressures compared with northern lineages, but in both regions these plants have undergone extensive extinction and range alteration over the Cenozoic (the last 66 Myr). It is not possible to observe the ecology of fossils directly, but indirect evidence of changes in bioclimatic envelopes can be derived from no‐analogue assemblages (i.e., groups of co‐occurring fossils that have climatically incongruous living relatives). We identify and examine the specific pairs of no‐analogue fossils within assemblages to disentangle the effects of climatic factors on past conifer extinctions and suggest which of these factors are likely to threaten southern conifer biodiversity in the future. Location Southern Hemisphere. Time period Cenozoic. Major taxa studied Conifers. Methods We use a recently developed method, “ hyperoverlap ”, to identify no‐analogue pairs of southern conifers. We characterize each pair in terms of temperature and precipitation and evaluate temporal patterns in no‐analogue pairs. These analyses represent a novel approach to studying both no‐analogue fossils and past changes in bioclimatic envelopes. Results We identified 240 no‐analogue pairs in the Cenozoic record of southern conifers. Most (75.4%) observations of no‐analogue pairs are likely to result from a change in the thermal (rather than hydrological) distribution between the fossil taxa and their extant counterparts, regardless of region or assemblage age. Thus, the fossil record shows some thermal lability, but strong hydrological stability in the tolerances of these plants. This implies that most southern conifers have inhabited wet climates through the Cenozoic, which is consistent with physiological evidence suggesting strong conservatism in drought tolerance. Main conclusions Southern conifers have adapted successfully to a wide range of temperatures, but future changes in rainfall are likely to pose the greatest threat to these plants, either directly or indirectly (e.g., through increased incidence of fire in mesic areas).

Application of machine learning to identify predators of stocked fish in Lake Ontario : using acoustic telemetry predation tags to inform management - Natalie V. Klinard; Jordan K. Matley; Silviya V. Ivanova; Sarah M. Larocque; Aaron T. Fisk; Timothy B. Johnson (Journal of Fish Biology, 2021)
Understanding predator–prey interactions and food web dynamics is important for ecosystem‐based management in aquatic environments, as they experience increasing rates of human‐induced changes, such as the addition and removal of fishes. To quantify the post‐stocking survival and predation of a prey fish in Lake Ontario, 48 bloater Coregonus hoyi were tagged with acoustic telemetry predation tags and were tracked on an array of 105 acoustic receivers from November 2018 to June 2019. Putative predators of tagged bloater were identified by comparing movement patterns of six species of salmonids ( i.e. , predators) in Lake Ontario with the post‐predated movements of bloater ( i.e. , prey) using a random forests algorithm, a type of supervised machine learning. A total of 25 bloater (53% of all detected) were consumed by predators on average (± S.D. ) 3.1 ± 2.1 days after release. Post‐predation detections of predators occurred for an average (± S.D. ) of 78.9 ± 76.9 days, providing sufficient detection data to classify movement patterns. Tagged lake trout Salvelinus namaycush provided the most reliable classification from behavioural predictor variables (89% success rate) and was identified as the main consumer of bloater (consumed 50%). Movement networks between predicted and tagged lake trout were significantly correlated over a 6 month period, supporting the classification of lake trout as a common bloater predator. This study demonstrated the ability of supervised learning techniques to provide greater insight into the fate of stocked fishes and predator–prey dynamics, and this technique is widely applicable to inform future stocking and other management efforts.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Long‐term retention of acoustic telemetry transmitters in temperate predators revealed by predation tags implanted in wild prey fish - Natalie V. Klinard; Jordan K. Matley; Aaron T. Fisk; Timothy B. Johnson (Journal of Fish Biology, 2019)
Bloater Coregonus hoyi ( n = 48) were implanted with V9DT‐2x predation transmitters and monitored on 105 acoustic receivers in eastern Lake Ontario for >6 months. Twenty‐three predation events were observed, with predator retention of tags ranging from ≤1 to ≥194 days and 30% of retentions lasting >150 days. Long tag retention times raise concerns for acoustic telemetry analysis and the health of piscivorous predators retaining tags.

Juvenile and adult leaves of heteroblastic Eucalyptus globulus vary in xylem vulnerability - Christopher J. Lucani; Timothy J. Brodribb; Greg J. Jordan; Patrick J. Mitchell (Trees, 2019)

Underaddressed animal‐welfare issues in conservation - Jordan O. Hampton; Timothy H. Hyndman (Conservation Biology, 2019)
Much progress has been made toward assessing and improving animal welfare in conservation. However, several glaring knowledge gaps remain where animal‐welfare concerns exist but animal‐welfare studies have not been performed in politically sensitive contexts. Based on contemporary issues in Australia, we identified 4 topics that require more research: animal‐welfare oversight for operations designated as management (as opposed to research); animal‐welfare impacts of biological agents used to control invasive animals; welfare of animals hunted recreationally; and animal‐welfare impacts associated with indigenous wildlife use. Animal‐welfare science may be applied to these sensitive topics through simple quantitative studies (e.g., quantifying the frequency of adverse animal‐welfare events). Several such studies have effectively addressed animal‐welfare concerns in similarly contentious contexts, including feral camel ( Camelus dromedarius ) culling in Australia, recreational hunting in Scandinavia, and indigenous whale hunting in the United States. For discussions of animal welfare in conservation to be evidence‐based, courageous research is required in the 4 key areas we identified.

Linking the Abundance of Estuarine Fish and Crustaceans in Nearshore Waters to Shoreline Hardening and Land Cover - Matthew S. Kornis; Denise Breitburg; Richard Balouskus; Donna M. Bilkovic; Lori A. Davias; Steve Giordano; Keira Heggie; Anson H. Hines; John M. Jacobs; Thomas E. Jordan; Ryan S. King; Christopher J. Patrick; et al. (Estuaries and Coasts, 2017)

Microglial Activation and Antioxidant Responses Induced by the Parkinson’s Disease Protein α-Synuclein - Dawn Béraud; Hannah A. Hathaway; Jordan Trecki; Sergey Chasovskikh; Delinda A. Johnson; Jeffrey A. Johnson; Howard J. Federoff; Mika Shimoji; Timothy R. Mhyre; Kathleen A. Maguire-Zeiss (Journal of Neuroimmune Pharmacology, 2013)

Resistance, resilience and recovery: aquatic bacterial dynamics after water column disturbance - Ashley Shade; Jordan S. Read; David G. Welkie; Timothy K. Kratz; Chin H. Wu; Katherine D. McMahon (Environmental Microbiology, 2011)
Summary For lake microbes, water column mixing acts as a disturbance because it homogenizes thermal and chemical gradients known to define the distributions of microbial taxa. Our first objective was to isolate hypothesized drivers of lake bacterial response to water column mixing. To accomplish this, we designed an enclosure experiment with three treatments to independently test key biogeochemical changes induced by mixing: oxygen addition to the hypolimnion, nutrient addition to the epilimnion, and full water column mixing. We used molecular fingerprinting to observe bacterial community dynamics in the treatment and control enclosures, and in ambient lake water. We found that oxygen and nutrient amendments simulated the physical‐chemical water column environment following mixing and resulted in similar bacterial communities to the mixing treatment, affirming that these were important drivers of community change. These results demonstrate that specific environmental changes can replicate broad disturbance effects on microbial communities. Our second objective was to characterize bacterial community stability by quantifying community resistance, recovery and resilience to an episodic disturbance. The communities in the nutrient and oxygen amendments changed quickly (had low resistance), but generally matched the control composition by the 10th day after treatment, exhibiting resilience. These results imply that aquatic bacterial assemblages are generally stable in the face of disturbance.

Contrasting Landscape Influences on Sediment Supply and Stream Restoration Priorities in Northern Fennoscandia (Sweden and Finland) and Coastal British Columbia - Jordan Rosenfeld; Daniel Hogan; Daniel Palm; Hans Lundquist; Christer Nilsson; Timothy J. Beechie (Environmental Management, 2011)

Trade‐Offs in the Design of Fishery Closures: Management of Silky Shark Bycatch in the Eastern Pacific Ocean Tuna Fishery - JORDAN T. WATSON; TIMOTHY E. ESSINGTON; CLERIDY E. LENNERT‐CODY; MARTIN A. HALL (Conservation Biology, 2009)
Bycatch—the incidental catch of nontarget species—is a principal concern in marine conservation and fisheries management. In the eastern Pacific Ocean tuna fishery, a large fraction of nonmammal bycatch is captured by purse‐seine gear when nets are deployed around floating objects. We examined the spatial distribution of a dominant species in this fishery's bycatch, the apex predator silky shark ( Carcharhinus falciformis ), from 1994 to 2005 to determine whether spatial closures, areas where fishing is prohibited, might effectively reduce the bycatch of this species. We then identified candidate locations for fishery closures that specifically considered the trade‐off between bycatch reduction and the loss of tuna catch and evaluated ancillary conservation benefits to less commonly captured taxa. Smoothed spatial distributions of silky shark bycatch did not indicate persistent small areas of especially high bycatch for any size class of shark over the 12‐year period. Nevertheless, bycatch of small silky sharks (